PENGEMBANGAN USAHA KECIL DAN MENENGAH (UKM) KERIPIK SINGKONG DAN KERIPIK GADUNG DI DUSUN KAUMAN, KEBUPATEN MOJOKERTO - Utama, Yoga; Rukismono, Martinus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
This activity is a Community Partnership Program (CPP) which to develop small and medium enterprises (SMEs) that related with culinary. They are UD. Dedi Jaya and UD. Dua Putri. Both of them are located in Kauman Village, Mojokerto Regency. UD. Dedi Jaya is a SME that sells fried cassava chips, while UD. Dua Putri are SME that selling raw asiatic bitter yam chips. The targets that achieved in this activity are improving the quality and quantity of products and marketing areas in both of them. For reaching the targets, UD. Dedi Jaya will be given an electric machine cassava cutters to increase the quantity of the product while the UD. Dua Putri will be given a stove and cooking utensils to improve the quality of their products into fried asiatic bitter yam chips. This is followed by making a hygienic kitchens so that the final product is more qualified. In addition, both SMEs will be created a media promotion which are websites that followed by training for using that media promotion to improve the marketing area for their products.